Anxiety, fear, and ontological security in world politics: thinking with and beyond Giddens. Issue 2 (July 2020) - Kinnvall, Catarina; Mitzen, Jennifer
Abstract : Research on ontological security in world politics has mushroomed since the early 2000s but seems to have reached an impasse. Ontological security is a conceptual lens for understanding subjectivity that focuses on the management of anxiety in self-constitution. Building especially on Giddens, IR scholars have emphasized how this translates to a need for cognitive consistency and biographical continuity – a security of 'being.' A criticism has been its so-called 'status quo bias, ' a perceived tilt toward theorizing investment in the existing social order. To some, an ontological security lens both offers social theoretic foundations for a realist worldview and lacks resources to conceptualize alternatives. We disagree. Through this symposium, we address that critique and suggest pathways forward by focusing on the thematic of anxiety. Distinguishing between anxiety and fear, we note that anxiety manifests in different emotions and leaves room for a range of political possibilities. Early ontological security scholarship relied heavily on readings of Giddens, which potentially accounts for its bias. This symposium re-opens the question of the relationship between anxiety and subjectivity from the perspective of ontological security, thinking with and beyond Giddens. Three contributions re-think anxiety in ontological security drawing on existentialist philosophy; two address limitations of Giddens' approach.